Updating knowledge on new medically important scorpion species in Mexico. (November 2017) - Riaño-Umbarila, Lidia; Rodríguez-Rodríguez, Everardo R.; Santibañez-López, Carlos E.; Güereca, Leopoldo; Uribe-Romero, Selene J.; Gómez-Ramírez, Ilse V.; Cárcamo-Noriega, Edson N.; Possani, Lourival D.; Becerril, Baltazar
Abstract: The increment in the number of scorpion envenoming cases in Mexico is mainly associated to the rapid growth of the urban areas, and consequently, to the invasion of natural habitats of these arachnids. On the other hand, there is a great diversity of scorpion species, so it is indispensable to identify those of medical importance, which we now know are many more than the 7–8 previously reported as dangerous to humans. Because different LD50 values have been reported for the venom of the same species, probably due to variations in the experimental conditions used, in this work we determined the LD50 values for the venoms of 13 different species of scorpions using simple but systematic procedures. This information constitutes a referent on the level of toxicity of medically important scorpion species from Mexico and establishes the bases for a more comprehensive assessment of the neutralizing capacity of current and developing antivenoms. Highlights: The total diversity of Mexican toxic scorpions has not been determined. We demonstrated that there are at least 13 medically important species. Systematic determination of venom LD50 revealed different levels of toxicity. These results will help to develop new anti-venoms.